University satellite institutes as exogenous facilitators of technology transfer ecosystem development - Marcus Conlé; Henning Kroll; Cornelia Storz; Tobias ten Brink (The Journal of Technology Transfer, 2021)
Universities can contribute to knowledge-based regional development not only in their home region but also in other regions. In a number of countries, universities have established university satellite institutes in additional (host) regions to promote research and technology transfer there. We investigate the role of university satellite institutes in the industrial development of regions, which, albeit not economically marginal, suffer from a weak knowledge infrastructure, limited absorptive capacities for external knowledge in the business sector and hence a low degree of attractiveness for non-local knowledge actors. Despite policy recommendations in favor of establishing satellite institutes, there has only been limited empirical research on this phenomenon, particularly concerning technology transfer ecosystem development. To fill this gap, we provide an exploratory case study of university satellite institutes in the Pearl River Delta of China's Guangdong province. We show how such institutes can be successful in facilitating the development of their host region's technology transfer ecosystems and demonstrate why they should be conceptually included in our existing understanding of third mission activities. Our research centers on the interplay of geographical proximity and non-spatial, organized proximity in the development of interregional knowledge bridges and entrepreneurial opportunities. We argue that the university's geographical proximity is only successful if the satellite institute, by facilitating organized proximity, promotes the geographical proximity of further knowledge actors, hereby propelling ecosystem development.
Keywords: I23; I28; L26; O3; R12; R58; 600; China; University technology transfer; Ecosystems; Innovation intermediaries; Peripheral regions